(untitled) (International Journal of Engineering and Computer Science, 2014)
It is the era of technology in which the world is developing. Therefore, people are highly dependent on carrying out their business (money) transactions through internet based services. Most of the fairing/billing systems are now available with online support. Hence to integrate all applications in one system we are introducing Universal Transport Billing System using RF-ID (Radio Frequency Identification) card. In public transportation system at present we use paper tickets which are printed by a small machine with a key pad. In this system we don’t know the details of passengers who are using the public transport. The details of the passenger are not taken in the existing system. The system requires user details in order to provide security during identification process. The details are also required in order to provide notifications via sms to the user. In our proposed system automatic ticketing is done with the help of RF-ID card. This card can be used for almost every transport system like buses, cabs, metros, auto-rickshaws and so on. It has details of passengers and it is placed on the RF-ID card reader and the destination is entered with the help of key pad. The amount is deducted from passenger’s account according to the distance the passenger as traveled respectively. Thus, users will not have to carry cash and the system becomes more convenient. The main advantage of the system is that the transaction & fare calculation is automated and secured. Disadvantage is the maintenance and the initial cost of installation for the system. The total system mainly acts to bring out the consistency in the public transport system that will conclude in uniform access of passengers in daily rides through an automated server being updated every single time the passengers travel by carrying the RFID based tickets.